A Retrospective Analysis of Thyroid Disease in Pregnancy at Chris Hani Baragwanath Academic Hospital Soweto South Africa - V Nicolaou; C Droste; K R L Huddle; C Dickens; C N Menezes; R Shires (South African Medical Association, 2017)
BackgroundThyroid diseases in pregnancy are associated with adverse outcomes for mother and fetus.No studies have been reported examining the spectrum and nature of such disorders in the Black population of South Africa.AimsTo examine thyroid disorders in pregnancy at Chris Hani Baragwanath Academic Hospital in Soweto, by assessing the causes, management and outcomes.MethodsA retrospective review of thyroid disorders was undertaken in 88 patients, attending the Antenatal Endocrine Clinic over a four-year period. All underwent initial and follow-up clinical and biochemical assessments.Maternal delivery records and thyroid function tests of the neonates 48 hours or later following delivery were reviewed.ResultsFifty-eight (66%) were hyperthyroid, 23(26%) hypothyroid, and 7(8%) had euthyroid colloid goiters. Forty-eight (83%) hyperthyroid patients had Graves’ disease, whilst had gestational hyperthyroidism. Regarding the hypothyroid patients, more than half followed I131 ablation for Graves’ disease. Eighty-seven percent of the hyperthyroid and 83% of the hypothyroid patients were euthyroid prior to delivery. One fatal maternal outcome, due to uterine rupture and six intra-partum fetal losses occurred. Amongst neonates, there was one case of a tracheo-esophageal fistula and one of neonatal thyrotoxicosis.ConclusionThis is the first report in sub-Saharan Africa detailing thyroid diseases in pregnancy.